2018
DOI: 10.1016/j.bja.2017.11.071
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer reliability of preoperative cardiopulmonary exercise test interpretation: a cross-sectional study

Abstract: Inter-observer reliability of interpretation of numerical values of two commonly used CPET variables was good (>80%). However, inter-observer agreement regarding the presence of a reportable value was less consistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
7
1
Order By: Relevance
“…A sample size calculation was performed using the sampicc function in STATA statistical software. Based on a previous study of Abbott et al, the estimated intraclass correlation coefficient (ICC) was 0.83 for V̇O 2VAT and 0.88 for V̇O 2peak [ 13 ]. It was hypothesized that the ICC values for the V̇E/V̇CO 2 -slope and OUES would be markedly higher, as interpretation of these parameters is less complex.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A sample size calculation was performed using the sampicc function in STATA statistical software. Based on a previous study of Abbott et al, the estimated intraclass correlation coefficient (ICC) was 0.83 for V̇O 2VAT and 0.88 for V̇O 2peak [ 13 ]. It was hypothesized that the ICC values for the V̇E/V̇CO 2 -slope and OUES would be markedly higher, as interpretation of these parameters is less complex.…”
Section: Methodsmentioning
confidence: 99%
“…Methods of determining the submaximal V̇O 2VAT are complex [ 12 ] and there remains controversy about the underlying physiology of the V̇O 2VAT [ 12 ]. A previous study has shown that the V̇O 2VAT is not determinable in approximately 16% of the preoperative CPETs [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the intraclass correlation coefficient (ICC) was used with a two‐way random‐effects model for absolute agreement, to measure the reliability of assignment of complication severity between the classification systems. This method is commonly used to compare the reliability of diagnostic tests. The ICC was calculated for the whole sample, and repeated after stratifying the sample by complication type.…”
Section: Methodsmentioning
confidence: 99%
“…The results are presented as ICC with 95 per cent confidence intervals. An ICC of zero suggests no agreement between classification systems, and an ICC of 1 suggests complete agreement. ICC values were interpreted based on the schema presented by Koo and Li: more than 0·90, excellent; 0·76–0·90, good; 0·50–0·75, moderate; less than 0·5, poor.…”
Section: Methodsmentioning
confidence: 99%